Effect of age, season and sire on semen quality traits in Frieswal breeding bulls - TYAGI, S; RAJA, T V; SIROHI, A S; CHAND, N; KUMAR, S; PANDE, M; MAHAJAN, S; KUMAR, S (The Indian Journal of Animal Sciences, 2023)
The present study was undertaken to assess the effect of season of semen collection, age and sire on semen quality of Frieswal breeding bulls. The data on 8113 semen ejaculates of 155 bulls born to 34 Frieswal sires were utilized for the study. The effect of age of bulls on semen volume, sperm concentration (million) per ml and sperm motility (%) in fresh semen (directly after collection) was highly significant. Additionally, it was discovered that the sire effect of bulls on different semen quality parameters and the influence of season on sperm concentration and motility both were statistically significant. Heritability estimates of different semen quality traits studied were moderately high and exceptionally significant. For semen volume, the estimate was found to be 0.336±0.078 while for concentration and pre freezing sperm motility values were 0.296±0.068 and 0.407±0.089, respectively. From the results, it may be concluded that the age and sire of bulls significantly affected the semen volume, sperm concentration and sperm motility in Frieswal bulls. The season of semen collection caused significant variations in sperm concentration and motility but not the semen volume. The semen volume and concentration were superior in ejaculates collected during winter season while the summer season was conducive for increased sperm initial motility. The Frieswal bulls up to 4-5 years are able to produce semen of better quality. The moderately high heritability estimates of semen quality traits provide indication for genetic improvement of the traits through selection.